Indutores de criação: percepções de jovens sobre as práticas em dança no projeto de extensão educadança e sua contribuição para o campo educacional em Igarapé-Açu/PA - CRUZ, Clene Lisboa da (2021)
The study aims to present research on adolescents and young people about dance practices and their contribution to the educational field in Igarapé-Açu / PA. It was developed with 18 adolescents and young people, in the age group of 13 and 19 years old, inhabitants of peripheral of the municipality of Igarapé-Açu, northeast of Para. The recent theoreticalmethodological framework is based on a qualitative approach based on action research, as a research instrument, an evaluation, a questionnaire and a feedback. The teaching evidence shows that a shared dance with a community made possible the construction and renaming of artistic knowledge and productions that emerged within the scope of the EDUCADANÇA project: interconnections in the school context, developed in the year 2017 in the municipality and later incorporated into the artistic work of adolescents young participants. The research was also carried out when it refers to the valorization, to the human being, to the young and the young, to the behavioral, social, educational and political retrovigations that make possible the confrontation of the daily questions of the people in situations of social vulnerability.